Immersive escapes: examining the impact of personality traits, perceived enjoyment, flow and trust on virtual reality technology adoption intentions in an emerging market - Paul Blaise Issock Issock; Abby Jacobs; Aaron Koopman (Cogent Business & Management, 2024)
The travel restrictions imposed during the Covid-19 pandemic have expedited the adoption of Virtual Reality (VR) technology as a substitute for traditional tourism experiences. This study delves into the impact of personality traits, perceived enjoyment, and anticipated flow state on the inclination to embrace Virtual Reality (VR) technology for tourism purposes in South Africa. Furthermore, this research probes into the moderating role of trust in VR technology within these relationships. Survey data from 361 millennial South African tourists were employed, with structural equation modelling and multi-group analysis as the primary analytical methods. Results highlight curiosity as a key personality trait influencing perceived enjoyment and flow state. Both perceived enjoyment and anticipated flow state significantly affect the intention to adopt VR technology for tourism. Notably, the role tourists' trust in VR technology is demonstrated as critical in the usage for tourism. This research offers unique insights into drivers of VR technology for tourism and have practical implications for destination marketing and tourism development, especially in culturally diverse emerging markets such as by South Africa.
Keywords: 650; Virtual reality; tourism; trust; adoption intentions; flow theory; personality traits